2020
DOI: 10.1136/bmjgh-2020-002879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terrorist attacks on access to maternal healthcare services: a national longitudinal study in Burkina Faso

Abstract: IntroductionMost of the literature on terrorist attacks’ health impacts has focused on direct victims rather than on distal consequences in the overall population. There is limited knowledge on how terrorist attacks can be detrimental to access to healthcare services. The objective of this study is to assess the impact of terrorist attacks on the utilisation of maternal healthcare services by examining the case of Burkina Faso.MethodsThis longitudinal quasi-experimental study uses multiple interrupted time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
0
31
2
Order By: Relevance
“…We conducted a quasi-experimental study nested in a panel study (SYNERGIE) which aims to assess the implementation and effects of universal healthcare policies in rural and semi-rural Burkina Faso [26]. The study area comprised four health districts (Banfora, Sindou, Leo, and Tenado) purposively selected based on security and location (rural settings with only small towns) [27]. The study area has a total estimated population of 988,447 within an area of 21,472 km 2 (Fig 1) [28].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…We conducted a quasi-experimental study nested in a panel study (SYNERGIE) which aims to assess the implementation and effects of universal healthcare policies in rural and semi-rural Burkina Faso [26]. The study area comprised four health districts (Banfora, Sindou, Leo, and Tenado) purposively selected based on security and location (rural settings with only small towns) [27]. The study area has a total estimated population of 988,447 within an area of 21,472 km 2 (Fig 1) [28].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Likewise, Nigeria ranked third among the countries with the highest impact of terrorism in the 2017 and 2020 global terrorism reports 101 102. Previous studies have reported that conflicts and terrorism can affect the delivery of RMNCH services 27 28 94 103–105. Finally, the emergence of the COVID-19 highlights the need for further research on the coverage of RMNCH services.…”
Section: Discussionmentioning
confidence: 97%
“…39 In areas where care is already restricted due to physical or socioeconomic barriers, terrorist attacks further limit access to appropriate antenatal care. 40 This vulnerable population can see benefits in morbidity and mortality rates from the implementation of targeted strategies to improve maternal and perinatal care in hostile or terrorist-prone environments. 41 Along with pregnant women and infants, children are particularly susceptible to the effects of violence, with restricted growth and development from indirect effects such as disruption of food, family, and social services.…”
Section: Discussionmentioning
confidence: 99%